Suppression of vibrations in strongly nonhomogeneous 2DOF systems - Costa, S. N. J. [UNESP]; Balthazar, José Manoel [UNESP] (Springer, 2009)
In this work we analyze the effects of an optimal linear control for nonlinear systems under the vibrations of a strongly nonhomogeneous nonlinear two-degree-of-freedom system with single anchor spring under condition of initial impact. We compare the results with those obtained for (a) when using only a passive broadband boundary controller which, in essence, corresponds to a one-way passive and almost irreversible energy flow from a heavy or main system to a nonlinear energy sink (NES), and (b) when using the nonlinear energy sink in combination with the optimal linear control for nonlinear system.
Keywords: Control of oscillations; Boundary controller; Active linear feedback control